Técnicas de estudio y logros de aprendizaje en estudiantes de sexto grado de primaria de la Institución Educativa Eleodoro Bustamante López N° 60826, Iquitos 2019 - Lopez Pizarro, Maisy Patricia (2021)
This research was developed with the main objective of determining the relationship between study techniques and learning achievements of sixth grade students of the Educational Institution for Minors N ° 60826 "Eleodoro Bustamante López" - Iquitos 2019 The research methodology used was basic, field, descriptive-correlational level, with a non-experimental, cross-sectional, quantitative-correlational design. The study population was made up of 46 students enrolled in 6th grade at the Educational Institution for Minors No. 60826 "Eleodoro Bustamante López" - Iquitos 2019. To evaluate the study techniques, the survey "study techniques" was used and to evaluate the learning achievements, the 2019 annual qualifications of the study subjects were used, which were registered in a registration form; Descriptive statistics were used to establish the relationship between variables and dimensions: frequencies, average (x) and percentage (%); For the hypothesis test, it was contrasted using the non-parametric Spearman Rho test to determine the degree of relationship between the two variables and the proposed dimensions, given that both variables were of ordinal qualitative measure, at a confidence level of the 95% and significance of 5%. The research results show the existence of a significant positive relationship between both variables, specifically obtaining the value of p = 0.695, with the probability of occurrence of 0.000 (statistically 0.001) being less than 0.05, there is a direct, positive and very correlation. significant between study techniques and learning achievements of study subjects.